Antioxidant properties, functional components, and sensory profile of green tea oatmeal cookies - Susanti, Siti; Nurwantoro; Wardhani, Dyah Hesti; Suryani, Ade Erma; Nisa, Khoirun; Katherinatama, Aldia; Asikin, Yonathan (Progress in Nutrition, 2025)
As a healthy snack, oat cookies (OC) are very popular. During its development, OC was fortified with other ingredients to improve functional quality, such as green tea, which is high in antioxidants, particularly flavonoids. Previous research has shown that OC-fortified green tea has chemical properties specifically in accordance with a healthy diet (high in fiber but low in fat). Thus, this study aimed to evaluate catechin, epigallocatechin gallate (EGCG), antioxidant activity, and sensory properties of green tea oatmeal cookies (GTOC) compared to commercial and control cookies. The five cookie samples tested included oat cookies (control), wheat cookies, GTOC 6%, GTOC Commercial A, and GTOC Commercial B Antioxidant activity was measured using the DPPH assay, while catechin and EGCG contents were analyzed using LC-MS with 4-hydroxybenzoic acid as an internal standard. β-Glucan content was determined through extraction, purification, and characterization using LC-MS. Nutritional composition, including moisture, ash, fat, protein, and carbohydrate content, was analyzed using proximate analysis, and sensory evaluation was conducted with 25 panelists using a 4-point hedonic scale. GTOC 6% had significantly higher catechin, EGCG, and antioxidant activity than other samples. Sensory evaluation showed that GTOC was the most preferred by panelists in terms of taste, texture, and overall acceptability. The results suggest that green tea fortification enhances the functional and sensory properties of oat cookies. Green tea fortification in oat cookies improves antioxidant content while maintaining high consumer acceptability. Therefore, green tea fortification in oat cookies could enhance antioxidant activity and functional properties while maintaining high consumer acceptability.